Micellization in a Mixed Alkali Soap System - Suhaimi, Hamdan; Kassim, Anuar; Che Rose, Laili (1992)
The solubility of sodium octanoate and sodium dodecyl sulphate (SDS) in the micelle was investigated by measuring the surface tension of the aqueous solution of surfactant mixture as a function of mole fraction of surfactants. Results indicate that the critical micelle concentration (cmc) of the mixed sU1factant falls between the cmc value of the two surfactants. The results also indicate that the rate of change of cmc value tends to be near the longer hydrocarbon chain molecule (SDS) with lower cmc value. Therefore it was concluded that the longer hydrophobic group of SDS is geometrically favour able for the micelle formation. In addition, the results indicate that SDS and sodium octanoate molecules mix ideally in the micelle solution.